Implementation of Differentiated Learning Through the Utilization of Audiovisual Media for Improving the Tolerance Attitude of Grade V Students In the Science and Technology Subject at SDN Lahuafu - Siti Norma Abd. Gafar; Misnah; Bau Ratu (Kirana Publisher (KNPub), 2025)
Study This aiming For describe implementation learning differentiate through utilization of audiovisual media in increase attitude tolerance student Class V of SDN Lahuafu on the subject Science lessons . Research This use approach qualitative descriptive with technique data collection through observation , interviews , and documentation . Research results show that the teacher was successful apply learning differentiate based on style learning and readiness students , as well as utilizing audiovisual media such as educational videos , animations and documentaries as tool help main . Learning implemented in a way collaborative in group heterogeneous , accompanied by discussion and reflection , which encourages student For value differences . Impact from the application This seen in the increase attitude tolerance students , such as value opinion friends , work The same in group , and show empathy . Approximately 89% of students show change behavior to more direction​ tolerant . Approach This proven effective No only in aspect cognitive , but also in strengthening character student .